1990
DOI: 10.1017/s0033291700036679
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological correlate of Eating Attitudes Test scores in female college students

Abstract: SynopsisEating Attitudes Test (EAT) scores of forty female college students were compared to their electrodermal activity (EDA) responses when offered a plate of chocolate chip cookies. A significant positive correlation was detected between the EAT scores and the skin conductivity measures associated with the presentation of food. Women with the highest EAT scores also exhibited the greatest sympathetic nervous system responses to a plate of cookies. This finding supports the conclusion that the EAT is capabl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
8
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 11 publications
2
8
0
Order By: Relevance
“…The hypothesis of the authors that anorexia might be a phobic disorder was therefore not borne out (Salkind et al, 1980). Later on, autonomic arousal induced by real food stimuli was assessed in a sample of female college students by Wilson and Mercer (1990). The subjects were offered a plate of cookies and it was found that their skin conductance responses correlated signi®cantly and positively with their score on the Eating Attitude Test (Garner and Gar®nkel, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…The hypothesis of the authors that anorexia might be a phobic disorder was therefore not borne out (Salkind et al, 1980). Later on, autonomic arousal induced by real food stimuli was assessed in a sample of female college students by Wilson and Mercer (1990). The subjects were offered a plate of cookies and it was found that their skin conductance responses correlated signi®cantly and positively with their score on the Eating Attitude Test (Garner and Gar®nkel, 1979).…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that, amongst high EAT scorers, exposure to fattening foods such as chocolate chip cookies is associated with greater arousal of the sympathetic nervous system, assessed in terms of electrodermal activity (Wilson & Mercer, 1990). It has been found that, amongst high EAT scorers, exposure to fattening foods such as chocolate chip cookies is associated with greater arousal of the sympathetic nervous system, assessed in terms of electrodermal activity (Wilson & Mercer, 1990).…”
Section: Discussionmentioning
confidence: 99%
“…In the current study, it was decided to use food as the threat-related stimulus since Wilson and Mercer (1990) found that exposure to ''forbidden'' food was associated with increased sympathetic nervous system activity in women scoring highly on the Eating Attitudes Test (EAT; Garner & Garfinkel, 1979). In the current study, it was decided to use food as the threat-related stimulus since Wilson and Mercer (1990) found that exposure to ''forbidden'' food was associated with increased sympathetic nervous system activity in women scoring highly on the Eating Attitudes Test (EAT; Garner & Garfinkel, 1979).…”
mentioning
confidence: 99%
“…There is a good example of the complexity of the meaning of the responses. Thus, an increase in skin conductance as a response to the smell and the presence of alcohol in alcoholics has been found (Staiger et al, 1999) as well as a response to the presence of chocolate cookies in people with food craving (Wilson & Mercer, 1990). However, the presentation of stimuli-related and not related to alcohol causes a similar skin conductance in alcoholics (Stormak et al, 1993), and considering the psychophysiological responses to food, restrictive and not restrictive people, have similar responses (Overduin et al, 1997).…”
Section: Psychophysiology Of Cravingmentioning
confidence: 97%